Pengaruh E-Service Quality, E-Trust, dan E-Customer Satisfaction terhadap E-Customer Loyalty Pengguna Traveloka di Jabodetabek - Hana Fatimah; Dita Puruwita; Prima Andriani (Indo Publishing, 2026)
This study was conducted to analyze the effect of E-Service Quality, E-Trust, and E-Customer Satisfaction on E-Customer Loyalty among Traveloka users in Jabodetabek. This study employed a quantitative research approach. The sampling technique used was non-probability sampling with a purposive sampling method. Data were collected through questionnaires distributed to 200 respondents who were active Traveloka users residing in the Jabodetabek area. Data were analyzed using IBM SPSS Statistics version 24. The results showed that, partially, E-Service Quality, E-Trust, and E-Customer Satisfaction each had a positive and significant effect on E-Customer Loyalty. Simultaneously, these three variables also had a positive and significant effect on E-Customer Loyalty. The findings indicate that E-Service Quality, E-Trust, and E-Customer Satisfaction are important factors in enhancing E-Customer Loyalty among Traveloka users in Jabodetabek.